Structural correspondence in Molyneux’s subjects - Cheng, Tony (Philosophy and the mind sciences, 2024)
The historical Molyneux’s question – roughly, whether congenital blind subjects can visually identify shapes in front of them right after being made to see – is having its renaissance in recent years (Ferretti and Glenney, 2021). While there have been many different formulations of it, and many attempted answers as well, no clear consensus has been reached. Moreover, although arguably both memory and imagination are involved in the process, their roles in the Molyneux’s task have not been adequately discussed. In this paper, I focus on a specific version of Molyneux’s question, propose a specific hypothesis in relation to that version, and sketch the roles of structural correspondence, memory, and imagination in the relevant hypothesis. One key moral of this discussion is that while Molyneux’s question has primarily been regarded as a perceptual puzzle, other kinds of mental episodes such as memory and imagination have to be taken into account as well in order to have a more satisfying answer to versions of Molyneux’s question (Macpherson and Dorsch, 2018).